2011
DOI: 10.1016/j.paid.2010.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating self-reflection and insight as self-conscious traits

Abstract: Abstract:Recent years have seen several new models of individual-differences in self-consciousness. The present research evaluated self-reflection and insight as types of self-focused attention. In the self-reflection and insight model, both traits represent metacognitive individual differences that aid self-regulation. In a sample of 233 young adults, both self-reflection and insight covaried with many different self-conscious traits (public and private self-consciousness, rumination, reflection), which sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 38 publications
1
44
1
6
Order By: Relevance
“…Higher insight predicted lower Beck Depression Inventory, Beck Anxiety Inventory, and Center for Epidemiological Studies Depression scores, higher Positive Affect, lower Negative Affect, and higher self-esteem (Silvia & Philips, 2011). Insight has significant negative relationships with private self-consciousness, public self-consciousness and rumination, insight did not significantly predict reflection (Silvia & Philips, 2011). Insight negatively correlated with measures of depression, anxiety, stress and alexithymia, and correlated positively with cognitive flexibility and self-regulation (Grant et al, 2002).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Higher insight predicted lower Beck Depression Inventory, Beck Anxiety Inventory, and Center for Epidemiological Studies Depression scores, higher Positive Affect, lower Negative Affect, and higher self-esteem (Silvia & Philips, 2011). Insight has significant negative relationships with private self-consciousness, public self-consciousness and rumination, insight did not significantly predict reflection (Silvia & Philips, 2011). Insight negatively correlated with measures of depression, anxiety, stress and alexithymia, and correlated positively with cognitive flexibility and self-regulation (Grant et al, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…ındividual with high insight has lower depression and anxiety symptoms, lower negative affect, higher positive affect and higher self-esteem (Silvia & Philips, 2011). Higher insight predicted lower Beck Depression Inventory, Beck Anxiety Inventory, and Center for Epidemiological Studies Depression scores, higher Positive Affect, lower Negative Affect, and higher self-esteem (Silvia & Philips, 2011). Insight has significant negative relationships with private self-consciousness, public self-consciousness and rumination, insight did not significantly predict reflection (Silvia & Philips, 2011).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Grant, Franklin, and Langford (2002, p. 821) defined self-reflection as 'the inspection and evaluation of one's thoughts, feelings, and behavior'. Self-reflection has a significant positive relationship with self-consciousness and it is central to cognitive skills such as self-regulation (Silvia and Phillips 2011).…”
Section: Psychological Determinantsmentioning
confidence: 99%
“…The relationship between self-reflection and self-insight is a complex one; research has found the concepts to be either negatively related or unrelated (Grant et al, 2002;Lyke, 2009;Silvia & Phillips, 2011). In contrast, Hixon and Swann (1993) found that self reflection leads to insight when aspects o f one's self-concept are readily accessible, when one is reflecting on "what one is" rather than "why one is," and when the amount o f reflection is Individuals using an informational identity processing style actively and objectively evaluate self-relevant information in forming and revising their self-definitions.…”
Section: Self-reflection and Insightmentioning
confidence: 99%